Fulminant Giant Cell Myocarditis and Cardiogenic Shock: An Unusual Presentation of Malignant Thymoma - Deepak Koul; Manreet Kanwar; Dane Jefic; Anuradha Kolluru; Tejwant Singh; Sunil Dhar; Preetham Kumar; Gerald Cohen (Cardiology Research and Practice)
Malignant thymoma is rarely associated with giant cell myocarditis. We present a case study that illustrates this association and cardiogenic shock with underlying tamponade. The dramatic presentation of this scenario has not been previously described.